Perilaku Belajar “AG” Anak Usia TK di Kelurahan Pahlawan Palembang - Sari, Karlina Mayang; Darmawani, Evia; Novianti, Rahmah (ANTHOR: Education and Learning Journal, 2023)
The formulation of the research problem is 1. Why is the "AG" learning behavior of kindergarten-aged children in the Pahlawan Palembang village slow in language development (writing and spelling), 2. What factors cause differences in interest in learning "AG". The purpose of the research conducted was to describe how the learning behavior of "AG" kindergarten-aged children in the Heroes Village of Palembang is slow in language development (writing and spelling). The main subjects in this study were 5-year-old children in one of the private tutoring places in the Pahlawan village of Palembang city. While the subject supports parents, private tutors, peers, and the community in the neighborhood. The object of this study is the learning behavior of "AG" which shows a slow interest in writing and reading, and the factors that cause it. Datacollection techniques in this study used observation and interviews. The data analysistechnique in this study uses data triangulation. Based on the results of the research thathas been stated, the factors that cause "AG" learning behavior are habituation patterns inthe family environment which allow "AG" to be free to play with gadgets all day long, andnot carry out stricter supervision from parents in playing gadgets which results in "AG". freely playing with his gadget.